Democratic Party Proxy for Attendance at the State Central Committee Meeting (1968)
This document is a Democratic Party proxy form for the State Central Committee meeting in Sacramento on August 11, 1968. Jane Tolmach designates Assemblyman J. K. "Ken" Mac Donald of Ojai, California, as her proxy with full authority to act on her behalf at the meeting. The form includes a declaration under penalty of perjury and notes that it must be filed with the Secretary of State by August 10, 1968.